THE EFFECT OF QUICK RATIO (QR), RETURN ON ASSET (ROA), DEBT TO EQUITY RATIO (DER), AND BOOK VALUE PER SHARE (BVS) ON STOCK PRICE OF COMPANIES LISTED IN JAKARTA ISLAMIC INDEX (JII) FOR THE 2017-2021 PERIODS - Nastiti, Nila Sari; Widodo, Saniman; Budiyono, Iwan (KEUNIS, 2023)
This study intends to examine the major simultaneous and partial effects of the Quick Ratio (QR), Return on Asset (ROA), Debt to Equity Ratio (DER), and Book Value per Share (BVS) on Stock Price.From 2017 through 2021, this study covered all businesses listed on the Indonesia Stock Exchange that is a part of the Jakarta Islamic Index (JII) group. The Eviews 10 program was used for the hypothesis testing. According to the needs of the research, A purposive sampling  method was used to choose a sample of companies. The tests' findings indicate that the Quick Ratio (QR), Return on Asset (ROA), Debt to Equity Ratio (DER), and Book Value per Share (BVS) all simultaneously affect stock price in a substantial way. On the stock price, QR has a partially favorable but negligible impact, ROA has a positively significant impact, DER has a negatively significant impact, and BVS has a positively significant impact.